Comparing Electrical Stimulation With and Without Ultrasound Guidance for Phenol Neurolysis to the Musculocutaneous Nerve. Issue 4 (15th September 2017) - Matsumoto, Mary E.; Berry, Jessica; Yung, Herbie; Matsumoto, Martha; Munin, Michael C.
Abstract: Background: Ultrasound guidance is increasingly being used for neurolytic procedures that have traditionally been done with electrical stimulation (e‐stim) guidance alone. Ultrasound visualization with e‐stim−guided neurolysis can potentially allow adjustments in injection protocols that will reduce the volume of neurolytic agent needed to achieve clinical improvement. Objective: This study compared e‐stim only to e‐stim with ultrasound guidance in phenol neurolysis of the musculocutaneous nerve (MCN) for elbow flexor spasticity. We also evaluated the ultrasound appearance of the MCN in this population. Design: Retrospective review. Setting: University hospital outpatient clinic. Participants: Adults (N = 167) receiving phenol neurolysis to the MCN for treatment of elbow flexor spasticity between 1997 and 2014 and adult control subjects. Methods: For each phenol injection of the MCN, the method of guidance, volume of phenol injected, technical success, improved range of motion at the elbow postinjection, adverse effects, reason for termination of injections, and details of concomitant botulinum toxin injection were recorded. The ultrasound appearance of the MCN, including nerve cross‐sectional area and shape, were recorded and compared between groups. Main Outcome Measures: The volume of phenol injected and MCN cross‐sectional area and shape as demonstrated by ultrasound. Results: The addition of ultrasound to e‐stim−guided phenol neurolysis was associated with lower doses of phenol when compared to e‐stim guidance alone (2.31 mL versus 3.69 mL, P < .001). With subsequent injections, the dose of phenol increased with e‐stim guidance ( P < .001), but not with e‐stim and ultrasound guidance ( P = .95). Both methods of guidance had high technical success, improved ROM at elbow postinjection, and low rates of adverse events. In comparing the ultrasound appearance of the MCN in patients with spasticity to that of normal controls, there was no difference in the cross‐sectional area of the nerve, but there was more variability in shape. Conclusions: Combined e‐stim and ultrasound guidance during phenol neurolysis to the MCN allows a smaller volume of phenol to be used for equal effect, both at initial and repeat injection. The MCN shape was more variable in individuals with spasticity; this should be recognized so as to successfully locate the nerve to perform neurolysis. Level of Evidence: IV